The Happiness Riddle and the Quest for a Good Life - Cieslik, Mark (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book examines the meaning of happiness in Britain today, and observes that although we face challenges such as austerity, climate change and disenchantment with politics, we continue to be interested in happiness and living well. The author illustrates how happiness is a far more contested, social process than is often portrayed by economists and psychologists, and takes issue with sociologists who often regard wellbeing and the happiness industry with suspicion, whilst neglecting one of the key features of being human - the quest for a good life. Exploring themes that question what it means to be happy and live a good life in Britain today, such as the challenges young people face making their way through education and into their first jobs; work life-balance; mid-life crises; and old age, the book presents nineteen life stories that call for a far more critical and ambitious approach to happiness research that marries the radicalism of sociology, with recent advances in psychology and economics.- Resumé vydavatel